Evaluation of Internal Bleaching with 35% Hydrogen Peroxide in Dentin Conditioned with 37% Phosphoric Acid and 17% EDTA. - Fernando Peña-Bengoa; Nicolás Dufey; Germán Buchheister (Universidad de Concepción., 2020)
Introduction: This study aimed to evaluate the effect of dentin surface treatment with 37% phosphoric acid or 17% ethylenedia-minetetraacetic acid (EDTA) before Internal Bleaching with 35% hydrogen peroxide using the walking bleach technique. Material and Methods: This experimental in vitro study used 66 human premolars extracted for orthodontic reasons, which were debrided, endodontically prepared, and pigmented with chromogens derived from blood decomposition. The samples were randomly divided into three groups (n=22). Group A: bleaching agent without dentin conditioning; group B: bleaching agent in dentin conditioned with phosphoric acid 37%; group C: bleaching agent in dentin conditioned with 17% EDTA. 4 applications of bleaching agent were used with a separation of 4 days between each session. The initial color (baseline) and after each application was determined by spectrophotometry, recording the CIE L*a*b* values and the total color variation between the initial parameters and the different evaluation times. Results: Data were statistically analyzed with the Wilcoxon test. This showed statistically significant differences for the total variation of the color between the study groups, with the control group in no case inferior to the rest. Conclusion: The application of 37% phosphoric acid increased the effectiveness of the bleaching agent when compared to 17% EDTA. However, these did not increase the effectiveness compared to the application of the bleaching agent without a previous dentin surface treatment.